Enhanced gas migration through permeable bubble networks within consolidated soft sediments. Issue 11 (20th August 2018) - Johnson, Michael; Peakall, Jeffrey; Jia, Xiaodong; Fairweather, Michael; Harbottle, David; Biggs, Simon; Hunter, Timothy N.
Abstract : Many consolidated sediments experience in situ gas generation from methanogenesis, corrosion, or radiolysis reactions and can retain bubbles for long periods. Particular interest is motivated by the retention and acute release of flammable hydrogen from nuclear legacy waste sludge. X‐ray computed tomography was employed to observe 0.07–10 mm bubble populations within 30–1112 Pa yield strength Mg(OH)2 sediments. High rates of partial coalescence were observed among sub‐millimeter microvoids, forming extensive bubble networks which spanned the 32 mm field of view. Lattice Boltzmann and Monte Carlo modeling demonstrated these networks to be highly pervious to gas, with effective diffusivities for hydrogen of 3.7–12.5 × 10 −5 m 2 s −1 . Continuous vessel‐spanning bubble networks, dynamic connectivity between ganglia of coalesced bubbles, Haines jumps, and composite diffusion through the gas and aqueous phase can account for enhanced gas migration over length‐scales of several meters, thus enabling chronic gas release from low‐intermediate strength sediments ( 10   Pa   ≲ τ ≲ 1 kPa) too strong for buoyant bubble ebullition and too weak for vertical channel formation. © 2018 The Authors. AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers. AIChE J, 64: 4131–4147, 2018